Exploratory and spatial learning abilities in two African mole-rats with different social system. - Mazoch, Vladimír (Jihočeská univerzita, 2008)
The goal of this study was to examine differences in the exploratory activity, spatial learning and memory between two strictly subterranean rodents with different social systems, solitary silvery mole-rat (Heliophobius argenteocinereus) and social giant mole-rat (Fukomys mechowii) in a maze resembling natural burrows. Although the giant mole-rats showed better performance in most of the parameters of the test, this could not be easily explained by superior learning abilities of social species. The differences found could be more attributed to different motivation in both species. The solitary mole-rat was remarkably more cautious and moved with lower velocity, spent more time in the maze, made more errors and traveled a longer path before reaching the reward box.
Exploratory and spatial learning abilities in two African mole-rats with different social system.
Keywords: African mole-rats; Bathyergidae; spatial navigation; exploration; memory; complex maze; social species